Ultra-rapid processing of high-hardness tungsten–copper nanocomposites. (1st March 2016) - Daoush, Walid M.; Yao, J.; Shamma, M.; Morsi, K.
Abstract: This paper discusses the fabrication of tungsten (W)–copper (Cu) nanocomposites via an ultra-rapid Current-Activated Melt Infiltration (CAMI) process to produce W–Cu nanocomposites for the first time in a matter of seconds. This was accomplished through a unique composite powder layer arrangement that promotes efficient resistive heating as compared to microscopically mixed powders. The effects of current intensity on the developed macro/micro- and nano-structure are discussed. Due to the short duration of processing and limited grain growth, the nanocomposites produced the highest hardness reported. Multiphysics modeling was used to obtain an insight into the temperature distribution immediately prior to Cu infiltration. Graphical abstract: